Photothermoelectric Effects in Nanoporous Silicon. Issue 13 (28th January 2016) - Lai, Yu‐Sheng; Tsai, Chao‐Yang; Chang, Chin‐Kai; Huang, Cheng‐Yin; Hsiao, Vincent K. S.; Su, Yuhlong Oliver
Abstract : The first observation of the photothermoelectric effect in a nanoporous silicon (NPSi) device indicates that the photocurrent is dependent on the position of light‐induced local heating from illumination at the Au‐electrode/NPSi interface.